أثر التعلم المبرمج باستخدام الحاسوب على تحسين مستوى الأداء لبعض مهارات التمرير والتصويب في كرة اليد - الشعلان، معن أحمد محمود; بني عطا، أحمد مصطفى (جامعة مؤتة, 2008)
هدفت هذه الدراسة لمعرفة أثر التعلم المبرمج باستخدام الحاسوب في تحسين مستوى الأداء لبعض مهارات التمرير والتصويب في كرة اليد، كما هدفت لمعرفة الفروق بين طريقتي التعلم المبرمج باستخدام الحاسوب والطريقة الاعتيادية المستخدمة في تعليم التمرير والتصويب في كرة اليد، حيث تكونت عينة الدراسة من مجموعة من طلاب مديرية التربية والتعليم في لواء المزار الجنوبي من طلاب الصف العاشر الأساسي للعام الدراسي 2005/2006م، لم يسبق لهم ممارسة لعبة كرة اليد مسبقاً، وقد قسموا إلى مجموعتين: مجموعة تجريبية وعددهم (10) طلاب استخدمت التعلم المبرمج باستخدام الحاسوب ومجموعة ضابطة وعددهم (10) طلاب تعلمت بالطريقة الاعتيادية، واستخدم الباحثان المنهج التجريبي نظراً لملاءمته أهداف الدراسة، وقد استخدم الباحثان الأساليب الإحصائية المناسبة لتحقيق أهداف الدراسة وفرضياتها وهي (Te tes)، والمتوسطات الحسابية، والانحرافات المعيارية. أظهرت النتائج فروقاً ذات دلالة إحصائية في القياس البعدى في مهارة التمرير من أعلى من الثبات والتمرير من أعلى من الجري والتصويب من الثبات، والتصويب من الجري والقفز باستخدام الحاسوب لصالح المجموعة التجريبية، بينما لم تظهر النتائج فروقاً ذات دلالة إحصائية في مهارة التصويب من مستوى الحوض عند المجموعتين. وقد أوصى الباحثان باستخدام طريقة التعلم المبرمج باستخدام الحاسوب في تعليم المهارات المختلفة بكرة اليد، وضرورة الاهتمام بتصميم البرمجيات الخاصة بكرة اليد بشكل خاص والألعاب الرياضية بشكل عام وإجراء دراسات مشابهة على ألعاب أخرى. The aim of the study is to investigate the effect of computer programmed learning on the idea of learning passing and scoring skills in handball. In addition, the study started to identify the differences between the methods of computer programmed learning and the applied traditional method in teaching the skills of passing and scoring in handball. The study sample was a group of Tenth Grade students in the years (2005 /2006) from Al Mazar Educational Directorate. Those students had not practiced handball before , and they were divided into two small groups. The experimental group consisted of 10 students using the method of computer programmed learning and the Control group was the controlling one consisted of 10 students taught by the traditional method. The researcher applied the experimental method to suit the survey aims. The researchers built a computer teaching program on the skills of passing and scoring in handball in away that contains adetailed explanation as well as pictures and movable short films. The researcher used statistic ways (e.g. averages, standard deviation and Z-Test) to achieve the aims of the study. The results of this study indicated that there were statistically significant difference indication differences in the dimension measurement of the passing skill from the highest constant point and the passing from running and the scoring from running and leaping by using computer for the benefit of the experimental group on where the previous term on the one hand, the findings did not show differences with a static indication in the pendulum skill of passing (i.e. passing inside and outside) and the scoring from the pelvis level in the two groups, The researchers recommended using the computer programmed learning in teaching the various skills in handball , and the findings suggest that more efforts should be put into improving conditions in designing special programs for handball in particular and other sport games in general. In addition similar surveys on other games are preferable.
Keywords: المهارات الرياضية -- الأردن -- طلاب المدارس الثانوية -- كرة اليد -- الألعاب الرياضية -- تنمية المهارات -- التعليم المبرمج -- التعليم بالحاسوب -- لاعبو كرة اليد -- البرامج الالكترونية -- تقييم الأداء